Community differences in business births and business growths - Bull, Ivan; Winter, Frederick (Journal of Business Venturing, 1991)
The published literature relating to the location of a business tends to support two different kinds of theories: (1) that business locations are selected to minimize costs; or (2) that decision-makers select locations because of personal preferences. This study attempts to find explanations as to why certain communities have grown faster than others, and to provide a model for the location decision of a start-up business. We find a negative correlation of two entrepreneurship measures to environmental factors that are usually considered to be desirable, i.e., health care and the environment, climate and terrain, recreation, and low crime. We find a weak correlation between community attitudes and the entrepreneurship measures. We also find a positive correlation of entrepreneurship with a high number of college graduates; a negative correlation when a high proportion of the population is over age 65. Population mobility and low unemployment are also positively correlated with the measures, but those factors seem at least as likely to be results as to be causes of business births and business growth. We believe that start-ups are vital for any community that wishes to grow, therefore the location decision of start-up businesses seems important. We propose a model of the location decision of a start-up, a model that emphasizes the individuality of the decision maker and the specific success requirements of the business. The driving force behind a start-up can be a decision-maker's desire for personal gain, a problem that begs a solution, or a solution that is looking for a problem. In some cases, the reason for starting a business will dictate its location. In other cases, success requirements of the business will dominate. We believe that researchers can gain a true understanding of the location decision only by considering both the preference of the decision-maker and the requirements of the specific business.